Insulator-to-metal transition in vanadium supersaturated silicon: variable-range hopping and Kondo effect signatures. (7th June 2016) - García-Hemme, E; Montero, D; García-Hernansanz, R; Olea, J; Mártil, I; González-Díaz, G
Abstract: We report the observation of the insulator-to-metal transition in crystalline silicon samples supersaturated with vanadium. Ion implantation followed by pulsed laser melting and rapid resolidification produce high quality single-crystalline silicon samples with vanadium concentrations that exceed equilibrium values in more than 5 orders of magnitude. Temperature-dependent analysis of the conductivity and Hall mobility values for temperatures from 10 K to 300 K indicate that a transition from an insulating to a metallic phase is obtained at a vanadium concentration between 1.1 × 10 20 and 1.3 × 10 21 cm −3 . Samples in the insulating phase present a variable-range hopping transport mechanism with a Coulomb gap at the Fermi energy level. Electron wavefunction localization length increases from 61 to 82 nm as the vanadium concentration increases in the films, supporting the theory of impurity band merging from delocalization of levels states. On the metallic phase, electronic transport present a dispersion mechanism related with the Kondo effect, suggesting the presence of local magnetic moments in the vanadium supersaturated silicon material.